Efficacy of a Combined Intramedullary, Periarticular Injection, and Intraarticular Tranexamic Acid Application on Postoperative Bleeding in Total Knee Arthroplasty: A Retrospective Case-Matched Study - Theerawit Hongnaparak; Khanin Iamthanaporn; Pakjai Tuntarattanapong; Varah Yuenyongviwat (Advances in Orthopedics)
Background. Topical tranexamic acid (TXA) has been widely used to reduce postoperative blood loss following total knee replacement (TKA). This study aimed to evaluate the effect of combined intramedullary, periarticular injection, and intraarticular TXA application in patients who underwent TKA as compared to those who did not. Methods. This was a retrospective case-matched study of 111 patients. We evaluated the transfusion rate and postoperative drainage of 56 patients who underwent TKA using combined topical tranexamic acid application (directly pushed into the femoral intramedullary canal and tibia base, with periarticular soft tissue injection and injected into the knee cavity via a drain tube) and the control group of 55 patients. Results. In the control and TXA groups, 7.14% and 1.81% of the patients received blood transfusions, respectively (p=0.176). The closed-suction drainage output at 0–8 h and total drainage output were significantly lower in the TXA group than those in the control group (p<0.001). Conclusion. Application of topical TXA with the combined method (intramedullary, periarticular injection, and intraarticular) in TKA decreases postoperative suction drainage and may reduce the need for postoperative blood transfusion.